2002
DOI: 10.1161/hs0102.100481
|View full text |Cite
|
Sign up to set email alerts
|

Extending Tissue Plasminogen Activator Use to Community and Rural Stroke Patients

Abstract: Background and Purpose-Guidelines for intravenous tissue plasminogen activator (tPA) use in stroke emphasize the importance of limiting its use to facilities with imaging capabilities and stroke expertise. This prospective case series set out to evaluate the safety of tPA use in patients referred from rural communities to a tertiary center. Methods-Prospective data of 82 consecutive patients treated with tPA in London, Ontario, were reviewed. Results-Twenty-three patients were transferred to London from a rura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
54
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 19 publications
3
54
0
Order By: Relevance
“…Three small-scale studies including a total of 502 patients reported a similar inverse association between ODT and DNT, yet the magnitude of time delay in these evaluations, conducted between 1997 and 2002, was more pronounced. [12][13][14] Moreover, recent analysis of data from "Get With The GuidelinesStroke" hospitals (presented at the 2009 International Stroke Conference but not yet published in full) 11 yielded a treatment delay highly consistent with that observed in our survey.…”
Section: Discussionsupporting
confidence: 79%
“…Three small-scale studies including a total of 502 patients reported a similar inverse association between ODT and DNT, yet the magnitude of time delay in these evaluations, conducted between 1997 and 2002, was more pronounced. [12][13][14] Moreover, recent analysis of data from "Get With The GuidelinesStroke" hospitals (presented at the 2009 International Stroke Conference but not yet published in full) 11 yielded a treatment delay highly consistent with that observed in our survey.…”
Section: Discussionsupporting
confidence: 79%
“…However, for intracerebral hemorrhage and ischemic stroke, time lost in transportation to the hub results in delays to enrollment and limits participation analogous to what was seen clinically in the ship and drip paradigm of tPA delivery for acute ischemic stroke patients in remote EDs. 14,15 This could be overcome by enrolling patients at the spokes and initiating research protocols before arriving at the hub. Although not all therapies would be feasible in this scenario, administration of a putative neuroprotectant may be possible.…”
Section: Discussionmentioning
confidence: 99%
“…12,14,[17][18][19][20][21] It has also been shown that educational programs for both the public and physicians increase the number of patients arriving at the hospitals within the time limits for thrombolysis. 22 In US stroke centers, up to 59% of the patients who presented within 24 hours of symptom onset arrived within 3 hours.…”
Section: Discussionmentioning
confidence: 99%
“…Similar analyses have already been performed for intravenous treatment. [17][18][19][20]27 Patients who were transferred directly to our stroke center were mostly residents of Bern or an area close to that vicinity. Their mean prehospital delay was 99 minutes.…”
Section: Discussionmentioning
confidence: 99%